Cognitive Bias and Unsafe Behaviors in High-Altitude Construction Workers Across Age Groups - Yingfeng Kuang; Xiaolong Chen; Haohao Yang; Hongfeng Zhang; Cora Un In Wong (Buildings)
The present study aims to investigate how the safety cognition bias of high-altitude workers in different age groups in the construction industry affects their unsafe behaviors. A theoretical framework involving safety cognition bias, risk-taking propensity, work experience, and unsafe behaviors was constructed. The empirical analysis was conducted using structural equation modeling. The results indicate that safety cognition bias has a significant positive effect on the unsafe behaviors of high-altitude workers. Risk-taking propensity plays a mediating role in this relationship, with partial mediation for the new generation of high-altitude workers and full mediation for the older generation. Moreover, work experience plays a crucial role in moderating the relationship between safety cognition bias and unsafe behaviors, specifically showing a significant moderating effect on the new generation of high-altitude workers, while its impact on the older generation is not significant. These findings provide theoretical support and practical guidance for reducing unsafe behaviors in high-altitude construction work, enhancing the safety management level of construction workers.